Optimizing critical care for the elderly in resource-limited setting: intensive care unit verses high dependency unit - Jamwal, Tilotma; Rao, Akshata; Chatterjee, Prasun; Makkar, Namrata (International Journal of Research in Medical Sciences, 2025)
This article delves into the comparative advantages of Intensive Care Units (ICUs) over High-Dependency Units (HDUs) for geriatric patients, particularly in settings with limited resources. It investigates how ICUs outperform HDUs in terms of clinical outcomes and economic efficiency. Recent studies highlight that ICUs offer superior monitoring and specialized care, resulting in significantly better health outcomes for elderly patients, especially those with severe comorbidities and complex medical conditions. Lower mortality rates and improved functional recovery post-discharge underscore the benefits of ICU care compared to HDUs. Moreover, the economic analysis emphasizes the importance of cost-effectiveness in resource-constrained environments, ensuring that investments in ICU facilities yield substantial improvements in patient outcomes. This article consolidates evidence to underscore the advantages of ICU care for geriatric patients, advocating for informed healthcare policies that prioritize ICU resources to maximize overall health benefits.